2020
DOI: 10.1021/acsomega.0c05131
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical Thiocyanation of Aryl Compounds via C–H Functionalization

Abstract: Aryl thiocyanate compounds are important building blocks for the synthesis of bioactive compounds and intermediates for several functional groups. Reported thiocyanation reactions via C−H functionalization have limited substrate scope and low RME. The ball-milling method reported here uses ammonium persulfate and ammonium thiocyanate as reagents and silica as a grinding auxiliary. It afforded aryl thiocyanates with moderate to excellent yields for a wide variety of aryl compounds (36 examples, 8−96% yield), su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 78 publications
0
12
0
Order By: Relevance
“…Preliminary attempts indicated that 3.0 equivalents of the oxidants were feasible for the transformation at ambient temperature, yielding 35 % of the para ‐selective thiocyanated product 2 a (Table 1, entries 1–3). Taking the solvent‐free mechanochemical method as a reference, we carried out the reaction with 3.0 equivalent of ammonium thiocyanate (NH 4 SCN), 3.0 equivalents of ammonium persulfate [(NH 4 ) 2 S 2 O 8 ] and SiO 2 in mortar [12] . Unfortunately, the reaction didn't work though by manual milling for 1 hour (Table 1, entry 4).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Preliminary attempts indicated that 3.0 equivalents of the oxidants were feasible for the transformation at ambient temperature, yielding 35 % of the para ‐selective thiocyanated product 2 a (Table 1, entries 1–3). Taking the solvent‐free mechanochemical method as a reference, we carried out the reaction with 3.0 equivalent of ammonium thiocyanate (NH 4 SCN), 3.0 equivalents of ammonium persulfate [(NH 4 ) 2 S 2 O 8 ] and SiO 2 in mortar [12] . Unfortunately, the reaction didn't work though by manual milling for 1 hour (Table 1, entry 4).…”
Section: Resultsmentioning
confidence: 99%
“…Taking the solvent-free mechanochemical method as a reference, we carried out the reaction with 3.0 equivalent of ammonium thiocyanate (NH 4 SCN), 3.0 equivalents of ammonium persulfate [(NH 4 ) 2 S 2 O 8 ] and SiO 2 in mortar. [12] Unfortunately, the reaction didn't work though by manual milling for 1 hour (Table 1, entry 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…144 In 2020, Malvestiti et al developed a mechanical protocol for the thiocyanation of aryl compounds via C-H functionalization. 145 Ball-mill reactions were all performed on a 0.2 mmol scale, without solvent, in short reaction times. The best conditions found for thiocyanation of orthoand metasubstituted anilines were to grind together anilines (1 equiv), ammonium thiocyanate (1.5 equiv.…”
Section: Sharma Et Al Developed a 3-component Reaction Leading Tomentioning
confidence: 99%
“…172 In 2020, Malvestiti et al developed a mechanical protocol for the thiocyanation of aryl compounds via C-H functionalization. 173 Ball-mill reactions were all performed on a 0.2 mmol scale, without solvent, in short reaction times. The best conditions found for thiocyanation of ortho-and meta-substituted anilines were to grind together anilines (1 equiv.…”
mentioning
confidence: 99%